DESAIN BANGUNAN BARU PADA KAWASAN PELESTARIAN DI SURABAYA - Timoticin Kwanda (Dimensi: Journal of Architecture and Built Environment, 2004)
After a period of property crash in 1997, later in 2001 the increase of economic growth has produced new infill building development or infill design in the heritage areas of Surabaya. According to some internationally known charters and recommendations, principles of new infill design in the heritage areas have been developed, such as the Recommendation concerning the Safeguarding and Contemporary Role of Historic Areas (UNESCO, 1976), the Washington Charter (1987), and the World Heritage Cities Management Guide (UNESCO, 1991). In general, the principles state that new infill design should be undertaken in an architectural style which is compatible with the surrounding character of buildings and the context. Unfortunately in Surabaya, some cases of new infill designs have damaged the character of the heritage areas. Therefore, in the future the city of Surabaya should ensuring that new infill design is appropriate by preparing design guidelines, conservation plan and conservation areas. Abstract in Bahasa Indonesia : Setelah kehancuran usaha propeti yang terjadi pada tahun 1997, pada tahun 2001 pertumbuhan ekonomi telah menghasilkan pembangunan bangunan baru atau infill design pada kawasan pelestarian di Surabaya. Berdasarkan beberapa piagam yang dikenal didunia, prinsip-prinsip desain bangunan baru pada kawasan pelestarian telah dikenal seperti The Recommendation concerning the Safeguarding and Contemporary Role of Historic Areas (UNESCO, 1976), The Washington Charter (1987), and The World Heritage Cities Management Guide (UNESCO, 1991). Secara umum, prinsip-prinsip ini menyatakan bahwa desain bangunan baru harus dilaksanakan dengan memperhatikan langgam arsitektur yang serasi dengan karakter dan konteks bangunan-bangunan disekitarnya. Namun sangat disayangkan bahwa di Surabaya beberapa kasus desain bangunan baru telah merusak karakter kawasan pelestarian. Oleh karena itu, pada masa yang akan datang kota Surabaya harus memastikan bahwa desain bangunan baru dilakukan sebagaimana mestinya dengan menyusun pedoman desain, rencana pelestarian dan kawasan pelestarian. Kata kunci: desain bangunan baru, kawasan pelestarian.